Diagoras, Bellerophon and the Siege of Olympus. (13th December 2016) - Whitmarsh, Tim
Abstract: A consensus has formed over the last 30 years that Diagoras was not really an atheist and that the famous Apopurgizontes Logoi were falsely attributed to him at a later stage. This note argues that the evidence is consistent with the view that Diagoras was indeed an atheist and did indeed compose the Apopurgizontes . Further hints in other sources allow us to reconstruct, albeit speculatively, aspects of Diagoras' thought and self-presentation.